Associations between angiogenic factors and intravoxel incoherent motion-derived parameters in diffusion-weighted magnetic resonance imaging of breast cancer. Issue 41 (15th October 2021) - Lee, Youn Joo; Kim, Sung Hun; Kang, Bong Joo; Son, Yo Han; Grimm, Robert
Abstract : Abstract: Intravoxel incoherent motion (IVIM) diffusion-weighted magnetic resonance imaging (MRI) can be used to estimate perfusion-related parameters, but these parameters may differ, based on the curve-fitting algorithm used for IVIM. Microvessel density (MVD) and vascular endothelial growth factor (VEGF) status are used as angiogenic factors in breast cancer. We aimed to investigate the relationship between MVD, VEGF, and intravoxel incoherent motion (IVIM)-derived parameters, obtained by 4 curve-fitting algorithms, in patients with invasive breast cancers. This retrospective study investigated IVIM-derived parameters, D (ie, tissue diffusivity), D * (ie, pseudodiffusivity), and f (ie, perfusion fraction), of 55 breast cancers, using 10 b values (range, 0–800 s/mm 2 ) and 4 curve-fitting algorithms: algorithm 1, linear fitting of D and f first, followed by D * ; algorithm 2, linear fitting of D and f and nonlinear fitting of D * ; algorithm 3, linear fitting of D and f, linear fitting of D *, and ignoring D contribution for low b values; and algorithm 4, full nonlinear fitting of D, f, and D * . We evaluated whole-tumor histograms of D, f, and D * for their association with MVD and VEGF. D * 10, D * 25, D * 50, D * mean, D * 75, D * 90, f10, and f25, derived using algorithm 3, were associated with VEGF expression ( P  = .043, P  = 0.012, P  = .019, P  = .024, P  = .044, P  = .041, P  = .010, and P  = .005, respectively). However, no correlation existed between MVD and IVIM-derived parameters. Perfusion-related IVIM parameters obtained by curve-fitting algorithm 3 may reflect VEGF expression.